Assessment of crop and weed management strategies prior to introduction of auxin-resistant crops in Brazil. (28th February 2021) - Oliveira, Maxwel C.; Lencina, Anelise; Ulguim, André R.; Werle, Rodrigo
Abstract: A stakeholder survey was conducted from April through June of 2018 to understand stakeholders' perceptions and challenges about cropping systems and weed management in Brazil. The dominant crops managed by survey respondents were soybean (73%) and corn (66%). Approximately 75% of survey respondents have grown or managed annual cropping systems with two to three crops per year cultivated in succession. Eighteen percent of respondents manage only irrigated cropping systems, and over 60% of respondents adopt no-till as a standard practice. According to respondents, the top five troublesome weed species in Brazilian cropping systems are horseweed (asthmaweed, Canadian horseweed, and tall fleabane), sourgrass, morningglory, goosegrass, and dayflower (Asiatic dayflower and Benghal dayflower). Among the nine species documented to have evolved resistance to glyphosate in Brazil, horseweed and sourgrass were reported as the most concerning weeds. Other than glyphosate, 31% and 78% of respondents, respectively, manage weeds resistant to acetyl-CoA carboxylase (ACCase) inhibitors and/or acetolactate synthase (ALS) inhibitors. Besides herbicides, 45% of respondents use mechanical, and 75% use cultural (e.g., no-till, crop rotation/succession) weed control strategies. Sixty-one percent of survey respondents adopt cover crops to some extent to suppress weeds and improve soil chemical and physical properties. Nearly 60% of survey respondents intend to adopt the crops that are resistant to dicamba or 2, 4-D when available. Results may help practitioners, academics, industry, and policy makers to better understand the bad and the good of current cropping systems and weed management practices adopted in Brazil, and to adjust research, education, technologies priorities, and needs moving forward.